BID links ferroptosis to mitochondrial cell death pathways - Sandra Neitemeier; Anja Jelinek; Vincenzo Laino; Lena Hoffmann; Ina Eisenbach; Roman Eying; Goutham K. Ganjam; Amalia M. Dolga; Sina Oppermann; Carsten Culmsee (Redox Biology, 2017)
Ferroptosis has been defined as an oxidative and iron-dependent pathway of regulated cell death that is distinct from caspase-dependent apoptosis and established pathways of death receptor-mediated regulated necrosis. While emerging evidence linked features of ferroptosis induced e.g. by erastin-mediated inhibition of the Xc- system or inhibition of glutathione peroxidase 4 (Gpx4) to an increasing number of oxidative cell death paradigms in cancer cells, neurons or kidney cells, the biochemical pathways of oxidative cell death remained largely unclear. In particular, the role of mitochondrial damage in paradigms of ferroptosis needs further investigation.In the present study, we find that erastin-induced ferroptosis in neuronal cells was accompanied by BID transactivation to mitochondria, loss of mitochondrial membrane potential, enhanced mitochondrial fragmentation and reduced ATP levels. These hallmarks of mitochondrial demise are also established features of oxytosis, a paradigm of cell death induced by Xc- inhibition by millimolar concentrations of glutamate. Bid knockout using CRISPR/Cas9 approaches preserved mitochondrial integrity and function, and mediated neuroprotective effects against both, ferroptosis and oxytosis. Furthermore, the BID-inhibitor BI-6c9 inhibited erastin-induced ferroptosis, and, in turn, the ferroptosis inhibitors ferrostatin-1 and liproxstatin-1 prevented mitochondrial dysfunction and cell death in the paradigm of oxytosis. These findings show that mitochondrial transactivation of BID links ferroptosis to mitochondrial damage as the final execution step in this paradigm of oxidative cell death. Keywords: Ferroptosis, BID, Mitochondria, CRISPR, Oxytosis, Neuronal death